Improvising improvisational change - Pinha e Cunha, Miguel; Vieira da Cunha, Joao (Henry Stewart Talks, 2010)
Change defined, The puzzling relationship between organizations and change, Change as a property of organizations, Assessing change, Organization as a property of change, Assessing organizations, Improvisation, Conclusion